2010
DOI: 10.1002/mats.201000034
|View full text |Cite
|
Sign up to set email alerts
|

Folding of Polyalanine into Helical Hairpins

Abstract: The variation of the secondary structure and dimensions of long PA peptides was examined by means of all‐atom MD simulations. It was found that on cooling, instead of straight helices, hairpin‐like structures with two and three parallel helical legs were formed. The exclusive population of hairpins in PA at room temperature was proved by the bimodality of the distribution functions of the end‐to‐end distance and the radius of gyration. The helix‐turn‐helix motif revealed in PA simulations is pertinent for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In contrast, polypeptides shorter than the critical length are less stable and form random coils. This result may explain why there are no single long alpha helices found in nature, but that they are almost exclusively found in the forms of coiled-coils, triple helices, and even higher-order helical structures [5,42,43]. Moreover, our results show how the favored alpha helix length is altered by changes to energy terms that define the molecular interactions.…”
Section: A Perspective From Length Dependent Alpha Helix Stabilitymentioning
confidence: 65%
“…In contrast, polypeptides shorter than the critical length are less stable and form random coils. This result may explain why there are no single long alpha helices found in nature, but that they are almost exclusively found in the forms of coiled-coils, triple helices, and even higher-order helical structures [5,42,43]. Moreover, our results show how the favored alpha helix length is altered by changes to energy terms that define the molecular interactions.…”
Section: A Perspective From Length Dependent Alpha Helix Stabilitymentioning
confidence: 65%
“…Recently, studies on the folding of polyalanine in vacuum (absence of solvent) have been performed using a molecular dynamics (MD) simulation technique. , It was found that aside from the environment, the structure of polyalanine peptides is greatly affected by the number of amino residues (refs and and references therein). In particular, the equilibrium between (i) a long α-helix and (ii) more compact conformations comprising two or more stacked α-helices joined by small coils and stabilized by short-range attraction between neighboring α-helices were investigated in detail .…”
Section: Introductionmentioning
confidence: 99%
“…[103][104] and AMBER. [105][106][107] The Jorgensen group [101][102] developed the all-atom OPLS FF where the key was to fit parameters to better reproduce the entire Ramachandran diagram for amino acids, rather than just individual potentials. Mac-Kerell et al 104 developed the all-atom CHARMM22 FF to reproduce quantum-chemical potential landscapes for small dipeptide fragments and improve the backbone parameters with the use of an energy correction map on the Ramachandran (φ,ψ) angles to achieve an almost perfect match with QM data (CHARMM27 103 FF).…”
Section: Molecular Dynamics (Md)mentioning
confidence: 99%
“…AMBER99φ 108 is a variant FF for helix-coil simulations and replaces the parameters of the φ dihedral angle in AMBER99 with that of the AMBER94 FF. Recently, Duan et al 107 introduced the AMBER03 version as they modified the AMBER99 FF by reparametrizing the charges and dihedral angle parameters based on accurate quantum-chemistry potentials together with an implicit solvent model. Most of these FFs have been widely applied for the modelling of poly-alanine peptides (or p(Ala)n with n denoting the number of residues) in vacuum and solutions.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 99%
See 1 more Smart Citation